Tourism village development study: Lesson learned from Flory Village, Sleman Regency, Yogyakarta - Ali Roziqin; Zharfa Syarafina (Masyarakat, Kebudayaan dan Politik, 2021)
Flory Village is one of the tourism villages based on ecotourism in Sleman Regency. The formation of Flory Village is inseparable from the role of tourism aware group (Pokdarwis). The existence of village tourism destinations has a positive impact on rural economic development and regional tourism. This study explores how Flory Village and the community manage tourism. This research used descriptive qualitative which were analyzed using the Miossec model through the components of transportation, facilities, attitudes towards tourists, and the role of stakeholders. The result is that there are two tourism village groups, namely Dewi Flory and Taruna Tani who have succeeded in developing their tourism potential based on their respective characteristics. Dewi Flory focuses on educational tourism, making salted eggs, nata de coco, vegetable gardening, and outbound tourism in three rides: water rides, dry rides, and mini forests. Furthermore, Taruna Tani focuses on agriculture, such as ornamental plants and fruits, and village culinary tours. The four lessons from the management of a tourism village by two Pokdarwis in Flory Village are consistent innovation, management commitment, utilization of local human resources, and collaboration with other parties.